Association Between Blood Pressure Variability and Short-Term Outcome After Intra-arterial Thrombectomy in Acute Stroke Patients With Large-Vessel Occlusion - Yang, Mengqi; Lu, Tao; Weng, Baohui; He, Yi; Yang, Hong (Frontiers in Neurology, 2021)
The optimal range of blood pressure variability (BPV) for acute stroke patients with large-vessel occlusion (LVO) remains unclear. This study investigated the association between BPV from admission through the first 24 h after intra-arterial thrombectomy (IAT) and short-term outcome in LVO patients. We retrospectively analyzed 257 consecutive patients with LVO stroke who were treated with IAT. BP values were recorded at 2-h intervals from admission through the first 24 h after IAT. BPV, as reflected by pulse pressure variability (PPV), was determined based on standard deviation (SD), coefficient of variation (CV), successive variation (SV), and the difference between maximum and minimum blood pressure (ΔBP; systolic BP minus diastolic BP). The association between BPV and clinical outcome (Modified Rankin Scale score at 90 days) was analyzed by multivariate logistic regression analysis. Of the 257 included patients, 70 had a good outcome at 3 months. PPV from admission through the first 24 h after IAT was independently associated in a graded manner with poor outcome [multivariable-adjusted odds ratios (95% confidence interval) for the highest of PPV were 43.0 (8.7–212.8) for SD, 40.3 (9.8–165.0) for CV, 55.0 (11.2–271.2) for SV, and 40.1 (8.0–201.9) for ΔBP]. The area under the receiver operating characteristic curve (95% confidence interval) of the PPV parameters were 0.924 (0.882–0.965) for SD, 0.886 (0.835–0.938) for CV, 0.932 (0.891–0.973) for SV, and 0.892 (0.845–0.939) for ΔBP, and the Youden index values were 0.740, 0.633, 0.759, and 0.756, respectively. In summary, BPV from admission through the first 24 h after IAT was independently associated with poor outcome at 3 months in patients with LVO, with greater variability corresponding to a stronger association. Thus, PPV may be a clinically useful predictor of functional prognosis in LVO patients treated with IAT.